Conflict in the land law under the federation structure - Awang, Adibah (2003)
This paper examines incidence of conflict in the Malaysian land law under a federation structure. Under this set-up created by the Federal Constitution, the supreme law of the country, Malaysia has a two-tier governmental structure â€“ Federal and State government. The Constitution delineates and demarcates the sphere within which the two level of government operates. In other words, it determines the powers of both the Federal and State government. The extent of which these powers are distributed is to be found in the Ninth Schedule of the Constitution. Basically, land and land-based resources are assigned to the state, meaning that each state government can legislate on land matters. A perusal of the legislative list in the Ninth Schedule of the Constitution# reveals that â€œlandâ€, â€œagricultureâ€, â€œforestryâ€, â€œlocal governmentâ€ and â€œturtles and riverine fishingâ€ are assigned to the State List, but, â€œtown and country planningâ€, â€œrehabilitation of mining landâ€, â€œhousingâ€, â€œdrainage and irrigationâ€ are placed under the concurrent list, meaning that, both the federal and state governments shares jurisdiction over these matters. On the other hand, environmental related matters appear in all parts of the legislative list of the Ninth Schedule. In other words land, land related matters and its resources does not exclusively belong to the states. Moreover, the Constitution in many instances allows federal intervention in land matters. In encouraging diversity in its land law it also promotes uniformity of law and policy by permitting federal intervention in land and land related matters. This federal intervention on grounds of achieving uniformity of land law and policy however, is not applicable to the two states of East Malaysia that is Sabah and Sarawak#. However, the federal government has in many circumstances# intervened in state matters, namely land law, on other grounds. An important hypothesis of this paper is that conflict in the land law is inevitable under this set-up. The division of power under the Ninth Schedule of the Constitution, a crucial element of the Malaysian federation structure, will also be discussed in this paper. The area of conflict ranges from conflict arising from the interpretation of the law, conflict between a federal law and a state law to the direct challenge by the state of the federal governmentâ€™s policy on land. With regard to the term â€œland lawâ€ represents a wider interpretation of land as compared to the perception and demarcation of land made by the Federal Constitution. This matter will also be discussed in this paper. The writer will begin by discussing the constitutional framework within which the two levels of government in Malaysia, that is federal and state, operate in relation to land law and policy. The writer hopes that by understanding the position of the LandLlaw that existed under a Federal system, it will contribute to a better understanding of the need for a uniform law and policy as a mean to sustainable land development.